ESP in Malaysia - The background and problems - Ng, Kwei Kuen (Journal of Modern Languages, 2001)
This article reviews the background to English for Specific Purpose (ESP) teaching at the tertiary level in Malaysia. and examines the role and requirementof the teacher as a facilitator of academic studies.